STRATEGI KEPALA SEKOLAH DALAM PENINGKATAN PRESTASI BELAJAR SISWA (STUDI KASUS DI SMPN 1 FAKFAK) - Suyitno Suyitno (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2017)
This study described (1) management to improve students ’ achievement, (2) factors affecting problems to increase students ’ achievement. This study used qualitative approach assigning Headmaster of SMPN 1 Fak-Fak and all the school-teachers as subject. Data were collected using observation, interview and document analysis. The findings were: (1) headmaster as a leader already promoted discipline, empowering teachers, having MGMP, and established conducive and clean work atmosphere; (2) headmaster as a manager, supervisor, and innovator implemented strategies of empowering, supervising, and developing innovative teaching models; (3) factors to decline management were: lack of tools and facilities, lack of awareness of teachers to increase teaching quality, un-accredited teachers, and irrelevant teachers with subject matters.